Development of bioelectrocatalytic activity stimulates mixed‐culture reduction of glycerol in a bioelectrochemical system. Issue 3 (26th March 2015) - Zhou, Mi; Freguia, Stefano; Dennis, Paul G.; Keller, Jürg; Rabaey, Korneel
Summary In a microbial bioelectrochemical system (BES), organic substrate such as glycerol can be reductively converted to 1, 3‐propanediol (1, 3‐PDO) by a mixed population biofilm growing on the cathode. Here, we show that 1, 3‐PDO yields positively correlated to the electrons supplied, increasing from 0.27 ± 0.13 to 0.57 ± 0.09 mol PDO mol−1 glycerol when the cathodic current switched from 1 A m−2 to 10 A m−2. Electrochemical measurements with linear sweep voltammetry (LSV) demonstrated that the biofilm was bioelectrocatalytically active and that the cathodic current was greatly enhanced only in the presence of both biofilm and glycerol, with an onset potential of −0.46 V. This indicates that glycerol or its degradation products effectively served as cathodic electron acceptor. During long‐term operation (> 150 days), however, the yield decreased gradually to 0.13 ± 0.02 mol PDO mol−1 glycerol, and the current–product correlation disappeared. The onset potentials for cathodic current decreased to −0.58 V in the LSV tests at this stage, irrespective of the presence or absence of glycerol, with electrons from the cathode almost exclusively used for hydrogen evolution (accounted for 99.9% and 89.5% of the electrons transferred at glycerol and glycerol‐free conditions respectively). Community analysis evidenced a decreasing relative abundance of Citrobacter in the biofilm, indicating a community succession leading to cathode independent processes relative to the glycerol. It is thus shown here that in processes where substrate conversion can occur independently of the electrode, electroactive microorganisms can be outcompeted and effectively disconnected from the substrate.